Formation of Theologians through (Academic) Writing - Katharina PENNER (Богословські роздуми: Східноєвропейський журнал богословʼя)
Theologizing in the Church is usually considered to be an oral activity. A beginning theologian who embarks on research in theology, therefore, often lacks the skills of communicating results of theologizing in written form. However, writing - academic, but not only - effectively fosters the development of one's own “voice”, the moving from an intuitive to intellectually reflected faith, from insecurity in an unfamiliar environment to gaining and expressing one’s authority in the academic community. The development of writing skills promotes a deeper understanding of theological ideas, forms the spiritual and intellectual “persona” of the theologian, and enables the integration into an academic community. Some methodologies for academic writing in theology are discussed: a disciplined and self-critical approach to self-editing, discussion seminars, mentoring by an experienced author. A theological researcher must learn to “live” in two different communities - the Church and the Academy - and write in different “languages”.